The Comparison of Oral Health Status between Psychotic and Non-Psychotic Mental Disorders Patients - Anang, Zhavira Dwiyanti; Bakri, Saekhol; Wardani, Natalia Dewi; Nasia, Avina Anin (Acta Odontologica Indonesia, 2025)
Background: Psychotic mental disorder characterized by psychotic symptoms such as delusions and hallucinations, while non psychotic mental disorder has no severe impairment to recognize reality. Both of these mental disorders are predicted to have differences in oral health, proved by oral health status assessments.Aim: To know the comparison of oral health status between psychotic and non psychotic mental disorders patients.Method: Cross-sectional study of 40 respondents and age criteria of 18 – 55 years old, patients with orthodontic appliances or diabetes mellitus were not included. DMF-T Index and OHI-S examinations were used as oral health status assessments. The statistical test was using the Mann-Whitney test. Significant differences (p<0,05) was obtained.Result: Psychotic mental disorder patients had higher median values (6,72; 2,16), compared to non psychotic mental disorder patients (3,00; 1,00) based on DMF-T Index (p=0,016) and OHI-S (p=0,000).Conclusion:  Psychotic mental disorder patients had worse oral health than non psychotic mental disorder patient based on DMF-T Index and OHI-S.